2018
DOI: 10.1063/1.5022389
|View full text |Cite
|
Sign up to set email alerts
|

Free energy study of H2O, N2O5, SO2, and O3 gas sorption by water droplets/slabs

Abstract: Understanding gas sorption by water in the atmosphere is an active research area because the gases can significantly alter the radiation and chemical properties of the atmosphere. We attempt to elucidate the molecular details of the gas sorption of water and three common atmospheric gases (NO, SO, and O) by water droplets/slabs in molecular dynamics simulations. The system size effects are investigated, and we show that the calculated solvation free energy decreases linearly as a function of the reciprocal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…3. This indicates that N 2 O 5 is preferentially solvated at the interface, which is consistent with previous studies using empirical potentials 18,19 and the weak hydration observed in our bulk simulations. From this, we estimate an evaporation rate of k e = 12.5 ns −1 .…”
Section: Interfacial Model For N2o5 Reactive Uptakesupporting
confidence: 93%
See 1 more Smart Citation
“…3. This indicates that N 2 O 5 is preferentially solvated at the interface, which is consistent with previous studies using empirical potentials 18,19 and the weak hydration observed in our bulk simulations. From this, we estimate an evaporation rate of k e = 12.5 ns −1 .…”
Section: Interfacial Model For N2o5 Reactive Uptakesupporting
confidence: 93%
“…Molecular simulations can in principle be used to gain microscopic insight into the reactive uptake of atmospheric gases into solution, but traditional theoretical methods are insufficient to reach the broad range of length and time scales required. 12 Classical force fields have been used to study the physical solvation of N 2 O 5 , 18,19 where it is computationally tractable to employ enhanced sampling methods and represent large inhomogeneous systems. However, existing potentials are not suitable to model chemical reactions, precluding a study of the hydrolysis reaction.…”
mentioning
confidence: 99%
“…Classical force fields, which are widely used in computer simulations because of their computational efficiency, have been employed in molecular dynamics (MD) simulations to study the hydration properties of N2O5. 5,23 However, due to their inherent approximations and limited accuracy, classical force fields might not be relied upon for quantitative predictions. In ab initio MD (AIMD), the configurations of a system are explored at a given thermodynamic condition with energies and forces computed on-the-fly from first-principles electronic structure calculations 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the rapid development of the supercomputers and computation chemistry, many researchers have investigated the strength of solute‐solute, solute‐solvent, and solvent‐solvent interactions in solution, to explain the solubility behavior by comparing the free energies. Various of theoretical models for the calculation of SFE have been proposed, such as the implicit solvent efficient, density functional theory (DFT), reference‐modified density functional theory (RMDFT), integral equation theory, energy representation method based on molecular dynamics (MD) simulation, and DFT interaction potentials with MD simulation (DFT‐MD) . Compared with all above‐mentioned methods, the standard approaches for calculating the SFE based on MD, either the free energy perturbation method or the thermodynamic integration method, are more widely applied, in virtue of theoretically higher accuracy .…”
Section: Introductionmentioning
confidence: 99%